Shared e-scooters and the promotion of equity across urban public spaces - a case study in Braga, Portugal - Dias, Gabriel (2023)
Shared e-scooters were introduced in urban public spaces as a way to promote a modal shift from cars in short-distance trips, as well as to improve sustainability, resilience, and equity in urban transport. However, the expansion of shared e-scooter services in 2019 proved that this mode of transport, without integrated planning strategies, can bring some problems to cities, which are related to the illegal parking of e-scooters, an increase in head injuries, and the lack of population diversity among users. Regarding the latest, this research work aims at conducting a case study in the city of Braga, Portugal to reveal who the actual and potential users of shared e-scooters are and how their socioeconomic profile (e.g., gender, age, income range, literacy, occupation) and usage patterns related to the ones found in other cities. For this, a revealed preference survey was deployed on the case study site, and the respondents’ profiles were statistically correlated with the socioeconomic characteristics of the city’s general population in order to assess if this mode of transport provides an equitable service. Results show that shared e-scooters are not equally used by people of different genders, ages, and income ranges. Information on e-scooter usage inequalities across the population is useful for the city to proceed with more socially equitable mobility policies.